Green Vessel Concept : Solar Panel Integration for Sustainable Onboard Energy Solutions - Dhimas Ardiansyah Surya Atmadja; Alia, Diana; Rizqi Aini Rakhman; Agus Dwi Santoso; Kuntoro Bayu Ajie (Pusat riset dan Inovasi Nasional, 2025)
This study analyzes the potential use of solar cells as a renewable energy source on the MV SARI INDAH. With the increasing demand for energy and the negative environmental impacts of fossil fuels, solar cells provide a promising eco-friendly alternative. The research focuses on developing a prototype system to charge batteries using solar power, converting DC power into AC for ship operations. The methodology includes measuring sunlight intensity, current, and output voltage, while also calculating the battery capacity and the ship’s electrical load. Tests were conducted at various tilt angles, with data recorded hourly over two days to assess performance. The results show that a 75° tilt angle yields the highest voltage, current, and power output when compared to other angles. Based on these findings, the study recommends installing solar panels at a 75° angle on the compass deck. The system design utilizes two panels positioned opposite each other, forming a 150° angle to optimize energy capture. This setup is capable of supplying power to key areas on the ship, such as seven lamps in the E/R 2nd Deck, Control Room, Emergency Generator Room, and CO₂ Room. The system is designed to meet the total daily energy demand of approximately 1,400 Wh, which can be efficiently fulfilled by eight solar cells rated at 50 Wp each, providing a sustainable and efficient energy solution for the vessel.